2019
DOI: 10.3390/bs9070071
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Consumer Preferences for Production Process Labeling Using Visual Attention Data

Abstract: A second-price auction with eye movement recordings was used to investigate consumer preferences for labels disclosing the presence and absence of specific types of insecticides and to explore the relationship between visual attention and consumer purchasing behaviors. Findings contribute to the literature in the following ways. First, visual attention pattern was endogenously determined by personal knowledge and pollinator conservation activities. Less knowledgeable or less engaged participants fixated more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Concerning the potential impact of neonicotinoids on pollinator health, pro-environmental groups have encouraged retailers to clearly label products treated with neonicotinoids (US-EPA, 2013). However, public awareness of neonicotinoids among consumers remains low [9][10][11] and the extent to which products treated with neonicotinoids will impact consumers' preferences is unknown. Regardless of low public awareness, research has indicated that consumers value pollinator conservation efforts [76][77][78].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Concerning the potential impact of neonicotinoids on pollinator health, pro-environmental groups have encouraged retailers to clearly label products treated with neonicotinoids (US-EPA, 2013). However, public awareness of neonicotinoids among consumers remains low [9][10][11] and the extent to which products treated with neonicotinoids will impact consumers' preferences is unknown. Regardless of low public awareness, research has indicated that consumers value pollinator conservation efforts [76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…However, in this paper, we are particularly interested in investigating the attitude-PEB relationship through exploring consumers' attitudes and their consumption behavior toward pollinator-friendly products. Meanwhile, testing the comparability between the online DCE and experimental auction samples also serves as a check for sample representativeness and consistency of findings with Wei et al [10,27].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations